Evidence for sweep signatures in antibiotic-resistant strains in three species of bacteria - Anjani Pradhananga; Lorena Benitez-Rivera; Candace Clark; Kaho H. Tisthammer; Pleuni S. Pennings (PeerJ)
Over the last decades antibiotic resistance has evolved and spread in many different bacterial species. From an evolutionary perspective, drug resistance is an adaptation to a new environment. Population genetic theory predicts that recent adaptations are associated with reduced diversity in the part of the population that carries the adaptive trait, due to a process known as selective sweeps. It is not known if this prediction holds for antibiotic resistance in bacterial species that infect humans. Here, we use a convenience sample of eight datasets covering three species of bacteria (Escherichia coli, Staphylococcus aureus and Enterococcus faecium). The eight datasets include multi locus sequence type information and antibiotic resistance phenotypes for between 53 to 1,094 patient samples and between three and 19 different antibiotics. Consistent with selective sweep theory, we find that, in most cases, sequence-type diversity amongst antibiotic-resistant bacterial strains is lower than amongst antibiotic-susceptible strains. Specifically, in 45 out of 59 comparisons (76%), resistant strains were significantly less diverse than susceptible strains. We also observe that while diversity is lower amongst resistant strains, in all cases there were at least several different sequence types amongst the resistant strains, which suggests that we are dealing here with soft sweeps rather than hard sweeps. Finally, we show that sequence-type diversity of antibiotic-resistant strains is lower if resistance is rare, compared to when resistance is common, which is consistent with rare resistance being due to fewer evolutionary origins. To summarize, our results show that for several different bacterial species, diversity of resistant strains is generally reduced, which is consistent with the evolution of resistance driven by selective sweeps stemming from a limited number of evolutionary origins. In future studies, more detailed analysis of such sweep signatures is warranted.